Polymer fine particle, powdery granular material, resin composition and molding

Polymer fine particles with an elastic body and graft portion, composed of specific units, address the issue of low-temperature impact resistance in resin compositions, achieving enhanced performance in molded articles and polyvinyl chloride blends.

JP2025010905APending Publication Date: 2025-01-23KANEKA CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023113205
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-10
Publication Date
2025-01-23

AI Technical Summary

Technical Problem

Conventional resin compositions containing polymer fine particles do not provide sufficient impact resistance at low temperatures, necessitating an improvement in this critical property.

Method used

The development of polymer fine particles with an elastic body and a graft portion, composed of specific alkyl acrylate and polyfunctional units, which are blended with a matrix resin to enhance low-temperature impact resistance.

Benefits of technology

The resulting molded articles exhibit excellent low-temperature impact resistance, as demonstrated by an IZOD test result of 27 kJ/m² or higher at 0°C, and possess superior powder properties when mixed with polyvinyl chloride.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025010905000001
    Figure 2025010905000001
Patent Text Reader

Abstract

To provide new polymer fine particles which can provide a molding excellent in low temperature impact resistance.SOLUTION: Polymer fine particles have an elastic body, and a graft part graft-coupled to the elastic body, wherein the graft part contains specific amounts of an alkyl acrylate unit and a polyfunctional unit as constitutional units.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to polymer fine particles, powder particles, a resin composition and a molded article. [Background technology]

[0002] 2. Description of the Related Art A technique for blending polymer fine particles into a resin for the purpose of modifying the resin (for example, improving the impact resistance) is known. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Publication No. 3-259942 [Patent Document 2] International Publication No. WO2017 / 038724 Summary of the Invention [Problem to be solved by the invention]

[0004] However, the above-mentioned conventional techniques are not sufficient in terms of the impact resistance at low temperatures of molded articles of resin compositions containing polymer fine particles, and there is room for further improvement.

[0005] One embodiment of the present invention has been made in consideration of the above problems, and an object of the invention is to provide novel polymer microparticles which can provide molded articles having excellent low-temperature impact resistance. [Means for solving the problem]

[0006] The present inventors conducted extensive research to solve the above problems and have now completed the present invention.

[0007] That is, one embodiment of the present invention includes the following configuration. [1] Polymer microparticles having an elastomer and a graft portion grafted to the elastomer, the graft portion containing alkyl acrylate units and polyfunctional units in a total amount of 90% by weight or more relative to 100% by weight of constituent units. [2] The polymer microparticles according to [1], wherein the elastomer contains one or more structural units selected from the group consisting of farnesene units, diene units other than the farnesene units, vinyl units and polyfunctional units. [3] The polymer microparticles according to [1], wherein the elastomer comprises (i) a farnesene unit and (ii) one or more structural units selected from the group consisting of a diene unit, a vinyl unit and a polyfunctional unit other than the farnesene unit. [4] The polymer microparticles according to [1] or [3], wherein the elastomer contains 5.0% by weight to 99.9% by weight of farnesene units, and contains a total of 0.1% by weight to 95.0% by weight of one or more types of structural units selected from the group consisting of diene units, vinyl units and polyfunctional units other than the farnesene units, based on 100% by weight of structural units. [5] The polymer microparticles according to [4], wherein the elastomer contains, based on 100% by weight of constituent units, 0% by weight to 95.0% by weight of diene units other than the farnesene units, 0% by weight to 50.0% by weight of the vinyl units, and 0% by weight to 20.0% by weight of the polyfunctional units. [6] The polymer microparticles according to any one of [1] to [5], wherein the alkyl acrylate unit in the graft portion is a butyl acrylate unit. [7] A powder or granular material comprising the polymer microparticles described in [1]. [8] A resin composition comprising (i) the polymer fine particles according to any one of [1] to [6] or the powdery material according to [7], and (ii) a matrix resin. [9] The resin composition according to [8], wherein the matrix resin is polyvinyl chloride.

[10] A molded article obtained by molding the resin composition according to [8] or [9]. Effect of the Invention

[0008] According to one embodiment of the present invention, there is an effect that it is possible to provide novel polymer microparticles which can provide molded articles having excellent low-temperature impact resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] An embodiment of the present invention will be described below, but the present invention is not limited thereto. The present invention is not limited to each configuration described below, and various modifications are possible within the scope of the claims. In addition, embodiments or examples obtained by combining the technical means disclosed in different embodiments or examples are also included in the technical scope of the present invention. Furthermore, new technical features can be formed by combining the technical means disclosed in each embodiment. All academic documents and patent documents described in this specification are incorporated herein by reference. In addition, unless otherwise specified in this specification, "A to B" representing a numerical range means "A or more (including A and greater than A) and B or less (including B and smaller than B)".

[0010] In this specification, an "X unit" contained in a polymer, copolymer, or resin means a "structural unit derived from an X monomer." For example, a "farnesene unit" means a "structural unit derived from a farnesene monomer."

[0011] [1. Polymer microparticles] The polymer microparticles according to one embodiment of the present invention have an elastomer and a graft portion grafted to the elastomer, and the graft portion contains alkyl acrylate units and polyfunctional units in a total amount of 90% by weight or more relative to 100% by weight of the constituent units.

[0012] In this specification, "polymer microparticles according to one embodiment of the present invention" may be referred to as "polymer microparticles of the present invention." Also, "powdered material according to one embodiment of the present invention" may be referred to as "powdered material of the present invention," "resin composition according to one embodiment of the present invention" may be referred to as "resin composition of the present invention," and "molded product according to one embodiment of the present invention" may be referred to as "molded product of the present invention."

[0013] The polymer microparticles have the above-mentioned structure, and therefore have the advantage of being able to provide a molded article having excellent low-temperature impact resistance. For example, a resin composition can be obtained by blending (adding) the polymer microparticles with any resin. The molded article obtained by molding the resin composition has the advantage of being excellent in low-temperature impact resistance.

[0014] Furthermore, since the polymer microparticles have the above-mentioned configuration, they also have the advantage of being able to provide powder particles with excellent powder properties. Powder particles with excellent powder properties have the advantage of providing good mixability between the powder particles and the matrix resin to be mixed. In particular, when mixing a powder matrix resin such as polyvinyl chloride (PVC) with a powder particle to modify the powder matrix resin such as polyvinyl chloride (PVC), it is preferable to use a powder particle with excellent powder properties.

[0015] In this specification, the term "a molded article has excellent low-temperature impact resistance" means that, when the molded article is subjected to impact resistance measurement as described in detail in the Examples below, the result of the IZOD test at 0°C is 27 kJ / m 2 That is, when the impact resistance of a molded article of a resin composition containing the present polymer fine particles is measured as described in detail in the Examples below, the result of the IZOD test at 0° C. is 27 kJ / m or more. 2 The above advantages are achieved.

[0016] (1-1. Elastic body) The elastomer is not particularly limited. The elastomer preferably contains one or more structural units selected from the group consisting of farnesene units, diene units other than the farnesene units, vinyl units, and polyfunctional units. This configuration has the advantage of being able to provide a molded product with even better low-temperature impact resistance and a powder with even better powder properties.

[0017] More preferably, the elastomer contains (i) a farnesene unit, and (ii) one or more constituent units selected from the group consisting of diene units other than the farnesene unit, vinyl units, and polyfunctional units.

[0018] Farnesene is a bio-derived diene monomer produced from biomass such as sugar cane using fermentation technology.

[0019] Therefore, when the elastomer contains farnesene units, it has the advantage that the amount of plastic used in the production of polymer microparticles (especially the elastomer) can be significantly reduced. Such an advantage also contributes to the achievement of, for example, Goal 12 "Ensure sustainable consumption and production patterns" and Goal 13 "Take urgent action to combat climate change and its impacts" of the Sustainable Development Goals (SDGs) advocated by the United Nations.

[0020] Examples of farnesene from which the "farnesene unit" is derived include α-farnesene and β-farnesene. The elastomer may contain only α-farnesene units, only β-farnesene units, or both α-farnesene units and β-farnesene units. Compared to α-farnesene, β-farnesene is easier to manufacture and therefore more readily available. Therefore, it is preferable that the elastomer contains only β-farnesene units as farnesene units. In other words, it is preferable that the farnesene units contained in the elastomer are composed of only β-farnesene units.

[0021] The elastomer preferably contains a diene unit other than the farnesene unit. When the elastomer contains a diene unit other than the farnesene unit, the resin composition containing the polymer microparticles can provide a molded article having excellent toughness and impact resistance. A molded article having excellent toughness and / or impact resistance can also be said to have excellent durability.

[0022] The diene monomer from which the "diene unit other than the farnesene unit" is derived can also be referred to as a conjugated diene monomer.

[0023] Examples of diene monomers from which the "diene units other than farnesene units" are derived include 1,3-butadiene, isoprene (also known as 2-methyl-1,3-butadiene), and 2-chloro-1,3-butadiene. These diene monomers may be used alone or in combination of two or more. Compared with diene monomers other than farnesene and 1,3-butadiene, 1,3-butadiene is versatile and easily available. Therefore, as the diene units other than farnesene units, 1,3-butadiene units are preferred.

[0024] The elastomer preferably contains a vinyl-based unit. This configuration has the advantage that the obtained polymer microparticles can provide a molded article having excellent impact resistance and transparency. In this specification, the term "vinyl-based monomer" from which the vinyl-based unit is derived means a monomer having only one vinyl group.

[0025] Examples of vinyl monomers from which vinyl units are derived include (a) vinyl arenes such as styrene, α-methylstyrene, monochlorostyrene, and dichlorostyrene; (b) vinyl carboxylic acids such as acrylic acid and methacrylic acid; (c) salts of the vinyl carboxylic acids (such as sodium acrylate); (d) esters of the vinyl carboxylic acids (such as alkyl (meth)acrylates); (e) vinyl cyanides such as acrylonitrile and methacrylonitrile; (f) vinyl halides such as vinyl chloride, vinyl bromide, and chloroprene; (g) vinyl acetate; and (h) alkenes such as ethylene, propylene, butylene, and isobutylene. The above-mentioned vinyl monomers may be used alone or in combination of two or more. In this specification, (meth)acrylate means acrylate and / or methacrylate.

[0026] Examples of esters of vinyl carboxylic acid include (a) alkyl (meth)acrylates such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, octyl (meth)acrylate, dodecyl (meth)acrylate, stearyl (meth)acrylate, and behenyl (meth)acrylate; (b) aromatic ring-containing (meth)acrylates such as phenoxyethyl (meth)acrylate and benzyl (meth)acrylate; (c) hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate and 4-hydroxybutyl (meth)acrylate; (d) glycidyl (meth)acrylates such as glycidyl (meth)acrylate and glycidyl alkyl (meth)acrylate; and (e) alkoxyalkyl (meth)acrylates. These (meth)acrylate monomers may be used alone or in combination of two or more.

[0027] In this specification, the term "alkyl (meth)acrylate" refers to a (meth)acrylate that does not contain a substituent other than an alkyl group. In this specification, for example, hydroxyalkyl (meth)acrylate and alkoxyalkyl (meth)acrylate are not included in the alkyl (meth)acrylate.

[0028] From the viewpoint of the low-temperature impact resistance of the molded body and the ease of manufacturing the elastomer, the elastomer preferably contains one or more vinyl units selected from the group consisting of methyl acrylate units, ethyl acrylate units, butyl acrylate units and butyl methacrylate units, more preferably one or more vinyl units selected from the group consisting of ethyl acrylate units and butyl acrylate units, and particularly preferably butyl acrylate units.

[0029] The elastic body preferably contains a polyfunctional unit. This configuration has the advantages of being able to provide a molded product having even better low-temperature impact resistance and excellent transparency, and being able to provide a powder or granular material having even better powder properties.

[0030] When a polyfunctional monomer is used in the production (polymerization) of an elastomer, an elastomer containing a polyfunctional unit can be obtained. The polyfunctional monomer can function as a crosslinking agent in the production (polymerization) of an elastomer. Therefore, an elastomer produced (polymerized) using a polyfunctional monomer, in other words, an elastomer containing a polyfunctional unit, can also be called a crosslinked elastomer.

[0031] The polyfunctional monomer from which the polyfunctional unit is derived can be said to be a monomer having two or more radically polymerizable reactive groups in the same molecule. The radically polymerizable reactive groups are preferably carbon-carbon double bonds.

[0032] The polyfunctional monomer from which the polyfunctional unit is derived does not include butadiene, and examples thereof include (meth)acrylates having an ethylenically unsaturated double bond, such as allyl (meth)acrylate, allyl alkyl (meth)acrylates, and allyloxy alkyl (meth)acrylates. Examples of monomers having two (meth)acrylic groups include ethylene glycol di(meth)acrylate, butylene glycol di(meth)acrylate (e.g., 1,3 butylene glycol di(meth)acrylate), butanediol di(meth)acrylate, hexanediol di(meth)acrylate, cyclohexane dimethanol di(meth)acrylate, and polyethylene glycol di(meth)acrylates. Examples of the polyethylene glycol di(meth)acrylates include triethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, and polyethylene glycol (600) di(meth)acrylate. Examples of monomers having three (meth)acrylic groups include alkoxylated trimethylolpropane tri(meth)acrylates, glycerol propoxy tri(meth)acrylate, pentaerythritol tri(meth)acrylate, and tris(2-hydroxyethyl)isocyanurate tri(meth)acrylate. Examples of alkoxylated trimethylolpropane tri(meth)acrylates include trimethylolpropane tri(meth)acrylate and trimethylolpropane triethoxy tri(meth)acrylate. Examples of monomers having four (meth)acrylic groups include pentaerythritol tetra(meth)acrylate and ditrimethylolpropane tetra(meth)acrylate. Examples of monomers having five (meth)acrylic groups include dipentaerythritol penta(meth)acrylate. Furthermore, examples of monomers having six (meth)acrylic groups include ditrimethylolpropane hexa(meth)acrylate, etc. Examples of polyfunctional monomers include diallyl phthalate, triallyl cyanurate, triallyl isocyanurate, and divinylbenzene, etc.

[0033] The polyfunctional unit contained in the elastomer is not particularly limited, but is preferably one or more selected from the group consisting of butylene glycol di(meth)acrylate units, allyl (meth)acrylate units, and divinylbenzene units, and more preferably butylene glycol di(meth)acrylate units. This configuration has the advantage of being able to provide a molded product with better low-temperature impact resistance and a powder product with better powder properties.

[0034] The elastomer may contain structural units other than structural units selected from the group consisting of farnesene units, diene-based units other than farnesene units, vinyl-based units and polyfunctional units.

[0035] The elastomer preferably contains at least one type of structural unit selected from the group consisting of farnesene unit, diene unit other than farnesene unit, vinyl unit and polyfunctional unit in a total of 60% by weight or more, more preferably 70% by weight or more, more preferably 80% by weight or more, more preferably 90% by weight or more, even more preferably 95% by weight or more, and particularly preferably 100% by weight.In other words, it is particularly preferable that the elastomer is composed only of at least one type of structural unit selected from the group consisting of farnesene unit, diene unit other than farnesene unit, vinyl unit and polyfunctional unit.An elastomer having such a structure has the advantage of being easy to manufacture.

[0036] The elastomer preferably contains 0 to 99.9% by weight of farnesene units, more preferably 1.0 to 99.9% by weight, more preferably 3.0 to 99.9% by weight, more preferably 5.0 to 99.9% by weight, more preferably 5.0 to 80.0% by weight, more preferably 5.0 to 60.0% by weight, even more preferably 5.0 to 40.0% by weight, even more preferably 6.0 to 20.0% by weight, and particularly preferably 7.0 to 15.0% by weight. This configuration has the advantages of (i) greatly reducing the amount of plastic used in producing the elastomer, and (ii) providing a molded product with even better low-temperature impact resistance.

[0037] In this specification, "containing 0% by weight of X units" means that the elastomer does not contain X units. For example, "containing 0% by weight of farnesene units in 100% by weight of constitutional units" means that the elastomer does not contain farnesene units.

[0038] The elastic body preferably contains 0 to 99.9% by weight of β-farnesene units, more preferably 1.0 to 99.9% by weight, more preferably 3.0 to 99.9% by weight, more preferably 5.0 to 99.9% by weight, more preferably 5.0 to 80.0% by weight, more preferably 5.0 to 60.0% by weight, even more preferably 5.0 to 40.0% by weight, even more preferably 6.0 to 20.0% by weight, and particularly preferably 7.0 to 15.0% by weight, based on 100% by weight of the structural units. This configuration has the advantage of being able to provide a molded product with even better low-temperature impact resistance.

[0039] The elastomer preferably contains, in total, 0.1% by weight to 100.0% by weight of one or more constituent units selected from the group consisting of diene units other than farnesene units, vinyl units, and polyfunctional units, more preferably 0.1% by weight to 99.0% by weight, more preferably 0.1% by weight to 97.0% by weight, more preferably 0.1% by weight to 95.0% by weight, more preferably 20.0% by weight to 95.0% by weight, more preferably 40.0% by weight to 95.0% by weight, more preferably 60.0% by weight to 95.0% by weight, even more preferably 80.0% by weight to 94.0% by weight, and particularly preferably 85.0% by weight to 93.0% by weight, out of 100% by weight of constituent units. An elastomer having such a configuration has the advantage of being easy to manufacture.

[0040] We will explain the case where the elastomer contains, based on 100% by weight of structural units, a total of 0.1% by weight to 100.0% by weight of one or more structural units selected from the group consisting of diene units other than farnesene units, vinyl units and polyfunctional units (hereinafter referred to as "Case A").

[0041] In case A, the elastomer preferably contains 0 to 100.0% by weight of diene units other than farnesene units, more preferably 0 to 95.0% by weight, even more preferably 1 to 95% by weight, even more preferably 5 to 95% by weight, and particularly preferably 10 to 95% by weight, out of 100% by weight of structural units. This configuration has the advantage that a molded article having excellent toughness and impact resistance can be provided, and an elastomer having this configuration is easy to manufacture.

[0042] In case A, the elastomer preferably contains 0 to 50.0% by weight of vinyl units, more preferably 1 to 45% by weight, even more preferably 5 to 45% by weight, and particularly preferably 10 to 45% by weight, based on 100% by weight of the constituent units. This configuration provides a molded product with excellent impact resistance and transparency, and has the advantage that the elastomer having this configuration is easy to manufacture.

[0043] In case A, the elastic body preferably contains 0 to 20.0% by weight of the polyfunctional unit, more preferably 0.1 to 15.0% by weight, even more preferably 0.5 to 13.0% by weight, and particularly preferably 1.0 to 10.0% by weight, based on 100% by weight of the constituent units. This configuration has the advantages of being able to provide a molded product with better low-temperature impact resistance and transparency, and being able to provide a powder product with better powder properties.

[0044] In the production of an elastomer, the monomers contained in the elastomer-forming monomer (monomer mixture) can be the origin of the structural units of the resulting elastomer. For example, when the polymerization conversion rate in the production of an elastomer is 100%, the monomer composition contained in the elastomer-forming monomer (monomer mixture) becomes the composition of the structural units of the resulting elastomer.

[0045] (Volume average particle size of elastic body) The volume average particle diameter of the elastic body is preferably 10 nm to 50 μm, more preferably 10 nm to 10 μm, more preferably 10 nm to 1 μm, more preferably 20 nm to 500 nm, more preferably 30 nm to 300 nm, even more preferably 40 nm to 200 nm, and particularly preferably 50 nm to 100 nm. When the volume average particle diameter of the elastic body is (i) 10 nm or more, an elastic body having a desired volume average particle diameter can be stably obtained, and when (ii) 50.00 μm or less, the impact resistance of the obtained molded body or cured product becomes good. When the volume average particle diameter of the elastic body is 100 nm or less, there is an advantage that a molded body having even better low-temperature impact resistance can be provided. The volume average particle diameter of the elastic body can be measured using a dynamic light scattering particle size distribution measuring device or the like using an aqueous latex containing the elastic body as a sample. The method for measuring the volume average particle diameter of the elastic body will be described in detail in the following examples.

[0046] (Ratio of elastic body) The proportion of the elastomer in the polymer microparticles is preferably 40% by weight to 97% by weight, more preferably 60% by weight to 96% by weight, further preferably 80% by weight to 95% by weight, and particularly preferably 85% by weight to 95% by weight, based on 100% by weight of the polymer microparticles as a whole. When the proportion of the elastomer in 100% by weight of the polymer microparticles is 40% by weight or more, the resin composition can provide a molded article having excellent toughness and impact resistance. When the proportion of the elastomer in 100% by weight of the polymer microparticles is 97% by weight or less, the polymer microparticles do not easily aggregate (are unlikely to aggregate), so the resin composition does not become highly viscous. As a result, the resin composition can be easily handled.

[0047] The "elastic body" of polymer particles is an elastomer that has been polymerized separately. 1 , Elastic body 2 , ..., and elastic body n The "elastic body" of the polymer microparticles may include a composite of the elastic body. 1 , Elastic body 2 , ..., and elastic body n In this manner, an elastomer (multi-stage polymerized elastomer) may be produced by multi-stage polymerization in which a plurality of elastomers (polymers) are polymerized in turn.

[0048] (1-2. Graft part) The polymer microparticles have a graft portion grafted to the elastomer. The graft portion can play various roles. The "various roles" include, for example, (a) improving the compatibility between the resin component in the resin composition and the polymer microparticles, (b) improving the dispersibility of the polymer microparticles in the resin composition and in the molded product, and (c) enabling the polymer microparticles to be dispersed in the form of primary particles in the resin composition and in the molded product.

[0049] The graft portion contains 90% by weight or more of alkyl acrylate units and polyfunctional units in total, based on 100% by weight of the structural units. This configuration has the advantage that it is possible to provide a molded product having excellent low-temperature impact resistance, and also to provide a powder or granular material having excellent powder properties.

[0050] The graft portion may contain 95% by weight or more of alkyl acrylate units and polyfunctional units in total, or may contain 100% by weight, of 100% by weight of the constituent units. In other words, the graft portion may be composed of only alkyl acrylate units, may be composed of only polyfunctional units, or may be composed of only alkyl acrylate units and polyfunctional units.

[0051] Specific examples of monomers from which alkyl acrylate units are derived include methyl acrylate, ethyl acrylate, propyl acrylate, and butyl acrylate.

[0052] The graft portion preferably contains one or more alkyl acrylate units selected from the group consisting of methyl acrylate units, ethyl acrylate units, and butyl acrylate units, more preferably one or more alkyl acrylate units selected from the group consisting of ethyl acrylate units and butyl acrylate units, and particularly preferably butyl acrylate units. This configuration has the advantage of being able to provide a molded product with superior low-temperature impact resistance. The alkyl acrylate units in the graft portion may be butyl acrylate units, or in other words, may be composed of only butyl acrylate units.

[0053] Specific examples of the polyfunctional monomer are the same as those explained in the section (Elastomer) above, so the explanation therefor is incorporated by reference and will not be repeated here.

[0054] Among the polyfunctional monomers, polyfunctional monomers that can be preferably used for polymerization of the graft portion include allyl methacrylate, ethylene glycol di(meth)acrylate, butylene glycol di(meth)acrylate, butanediol di(meth)acrylate, hexanediol di(meth)acrylate, cyclohexanedimethanol di(meth)acrylate, and polyethylene glycol di(meth)acrylates. These polyfunctional monomers may be used alone or in combination of two or more.

[0055] When a polyfunctional monomer is used in the preparation (polymerization) of the graft portion, a graft portion containing a polyfunctional unit can be obtained. The polyfunctional monomer can function as a crosslinking agent in the preparation (polymerization) of the graft portion. Therefore, a graft portion prepared (polymerized) using a polyfunctional monomer, in other words, a graft portion containing a polyfunctional unit, can also be called a crosslinked graft portion.

[0056] The graft portion preferably contains 60.0 to 99.9% by weight of alkyl acrylate units, more preferably 70.0 to 99.9% by weight, even more preferably 80.0 to 99.9% by weight, even more preferably 90.0 to 99.9% by weight, even more preferably 95.0 to 99.9% by weight, and particularly preferably 98.0 to 99.9% by weight, based on 100% by weight of the structural units. This configuration has the advantage of being able to provide a molded product with excellent low-temperature impact resistance.

[0057] The graft portion preferably contains 60.0 to 99.9% by weight of butyl acrylate units, more preferably 70.0 to 99.9% by weight, even more preferably 80.0 to 99.9% by weight, even more preferably 95.0 to 99.9% by weight, and particularly preferably 98.0 to 99.9% by weight, based on 100% by weight of the structural units. This configuration has the advantage of being able to provide a molded product with even more excellent low-temperature impact resistance.

[0058] The graft portion preferably contains 0.1 to 40.0% by weight of the polyfunctional unit, more preferably 0.1 to 30.0% by weight, even more preferably 0.1 to 20.0% by weight, even more preferably 0.1 to 10.0% by weight, even more preferably 0.1 to 5.0% by weight, and particularly preferably 0.1 to 2.0% by weight, based on 100% by weight of the constituent units. This configuration has the advantage of being able to provide a powder or granule with excellent powder properties.

[0059] (Proportion of graft area) The proportion of the graft portion in the polymer microparticles is preferably 3% by weight to 60% by weight, more preferably 4% by weight to 40% by weight, further preferably 5% by weight to 20% by weight, and particularly preferably 5% by weight to 15% by weight, based on 100% by weight of the polymer microparticles as a whole. When the proportion of the graft portion in 100% by weight of the polymer microparticles is 3% by weight or more, it is advantageous that a powdered or granular material having more excellent powder characteristics can be provided. When the proportion of the graft portion in 100% by weight of the polymer microparticles is 60% by weight or less, it is advantageous that a molded product having more excellent low-temperature impact resistance can be provided.

[0060] The "grafted parts" of the polymer microparticles are each polymerized separately. 1 , graft part 2 , ..., and the graft section n The "graft portion" of the polymer fine particles may include a composite of the above. 1 , graft part 2 , ..., and the graft section n It may contain one polymer (multi-stage polymerization graft portion) obtained by multi-stage polymerization of the above.

[0061] In the production of the polymer microparticles, the elastomer and the graft portion may be polymerized in this order. In other words, the elastomer and the graft portion are polymerized in multiple stages. The polymer microparticles obtained by multistage polymerization of the elastomer and the graft portion can also be called multistage polymers.

[0062] When the polymer microparticles are multistage polymers, the elastomer and the graft portion may form a layer structure. For example, one embodiment of the present invention is one in which the elastomer forms the innermost layer (also referred to as a core layer) and the layer of the graft portion is formed as the outermost layer (also referred to as a shell layer) on the outside of the elastomer. A structure in which the elastomer is the core layer and the graft portion is the shell layer can also be called a core-shell structure. Thus, polymer microparticles in which the elastomer and the graft portion form a layer structure (core-shell structure) can also be called multilayer polymers or core-shell polymers. That is, in one embodiment of the present invention, the polymer microparticles may be multistage polymers and / or multilayer polymers or core-shell polymers.

[0063] In the polymer microparticles, it is sufficient that at least a portion of the graft portion covers at least a portion of the elastomer, and it is not necessary for the graft portion to cover the entire elastomer. A portion of the graft portion may (i) be graft-bonded to a graft portion that is graft-bonded to the elastomer, or (ii) may be embedded inside the elastomer. The graft portion may also cover the entire elastomer.

[0064] (1-3. Physical properties of polymer particles) (Volume average particle size of polymer particles) The volume average particle diameter of the polymer microparticles is not particularly limited, but is preferably 10 nm to 50 μm, more preferably 10 nm to 10 μm, more preferably 10 nm to 1 μm, more preferably 20 nm to 500 nm, more preferably 30 nm to 300 nm, even more preferably 40 nm to 200 nm, and particularly preferably 50 nm to 100 nm. When the volume average particle diameter of the polymer microparticles is (i) 10 nm or more, polymer microparticles having a desired volume average particle diameter can be stably obtained, and when (ii) 50.00 μm or less, the heat resistance and impact resistance of the obtained molded body or cured product are good. When the volume average particle diameter of the polymer microparticles is within the above range, there is also an advantage that the dispersibility of the polymer microparticles in the resin composition is good. In addition, when the volume average particle diameter of the polymer microparticles is 100 nm or less, there is an advantage that a molded body having particularly excellent low-temperature impact resistance can be provided. In this specification, the "volume average particle diameter of polymer microparticles" refers to the volume average particle diameter of primary particles of polymer microparticles, unless otherwise specified. The volume average particle diameter of polymer microparticles can be measured by a method described in detail in the following examples using an aqueous latex containing polymer microparticles as a sample. The volume average particle diameter of polymer microparticles can also be measured by cutting a molded product of a resin composition, photographing the cut surface using an electron microscope or the like, and using the obtained photographed data (photographed image).

[0065] (1-4. Method for producing polymer microparticles) The polymer fine particles can be produced by polymerizing an elastomer, and then graft polymerizing a polymer that constitutes a graft moiety onto the elastomer in the presence of the elastomer.

[0066] The polymer microparticles can be produced by known methods, such as emulsion polymerization, suspension polymerization, and microsuspension polymerization. Specifically, the polymerization of the elastomer in the polymer microparticles and the polymerization of the graft portion (graft polymerization) can be carried out by known methods, such as emulsion polymerization, suspension polymerization, and microsuspension polymerization. Among these, the emulsion polymerization method is particularly preferred as a method for producing polymer microparticles. By producing polymer microparticles by emulsion polymerization, latex (e.g., aqueous latex) containing polymer microparticles can be obtained. The emulsion polymerization method has the advantages of (i) easy composition design of the polymer microparticles, and (ii) easy industrial production of the polymer microparticles.

[0067] When emulsion polymerization is employed as a method for producing polymer fine particles, a known emulsifier (dispersant) can be used as the emulsifier (dispersant) for producing the polymer fine particles.

[0068] Examples of emulsifiers include anionic emulsifiers, nonionic emulsifiers, polyvinyl alcohol, alkyl-substituted cellulose, polyvinylpyrrolidone, polyacrylic acid derivatives, etc. Examples of anionic emulsifiers include sulfur-based emulsifiers, phosphorus-based emulsifiers, sarcosinic acid-based emulsifiers, carboxylic acid-based emulsifiers, etc. Examples of sulfur-based emulsifiers include sodium dodecylbenzenesulfonate (abbreviation: SDBS), sodium lauryl sulfate, etc. Examples of phosphorus-based emulsifiers include sodium polyoxyethylene lauryl ether phosphate, tripotassium phosphate, etc. Examples of carboxylic acid-based emulsifiers include sodium oleate, etc.

[0069] When the emulsion polymerization method is used as the method for producing the polymer microparticles, known thermal decomposition initiators such as organic peroxides can be used for producing the polymer microparticles. Examples of the organic peroxides include t-butylperoxyisopropyl carbonate, paramenthane hydroperoxide, cumene hydroperoxide, dicumyl peroxide, t-butyl hydroperoxide, di-t-butyl peroxide, and t-hexyl peroxide.

[0070] A redox type initiator can also be used to produce polymer microparticles. The redox type initiator is a combination of (a) a peroxide, such as an organic peroxide or an inorganic peroxide, and (b) ferrous sulfate (FeSO 4 7H 2 O), and / or a reducing agent such as sodium formaldehyde sulfoxylate or glucose. Together with these substances, a chelating agent such as disodium ethylenediaminetetraacetate, and a phosphorus-containing compound such as sodium pyrophosphate may be used in combination as necessary.

[0071] When a redox type initiator is used, polymerization can be performed even at a low temperature where the peroxide does not substantially decompose thermally, and the polymerization temperature can be set in a wide range. Therefore, it is preferable to use a redox type initiator as a polymerization initiator for producing polymer microparticles. Among redox type initiators, redox type initiators using organic peroxides such as cumene hydroperoxide, dicumyl peroxide, paramenthane hydroperoxide, and t-butyl hydroperoxide as peroxides are preferable. The amount of the initiator used, and the amount of the reducing agent, transition metal salt, and chelating agent used when a redox type initiator is used, can be within a known range.

[0072] When a polyfunctional monomer is used in the polymerization of the elastomer or the graft portion for the purpose of introducing a crosslinked structure into the elastomer or the graft portion, a known chain transfer agent can be used in a known amount range. By using the chain transfer agent, the molecular weight and / or degree of crosslinking of the obtained elastomer or the graft portion can be easily adjusted.

[0073] In the production of the polymer microparticles, in addition to the above-mentioned components, a surfactant may be further used. The type and amount of the surfactant used are within the known ranges.

[0074] In the production of polymer microparticles, the polymerization conditions such as polymerization temperature, pressure, and deoxidation may be appropriately set within known numerical ranges.

[0075] When polymer microparticles are obtained by emulsion polymerization, a suspension (also called aqueous latex) containing polymer microparticles dispersed in the form of primary particles in an aqueous dispersion medium can be obtained. Using such a suspension, the polymer microparticles can be aggregated by a known method, and the polymer microparticles can be collected. The collected polymer microparticles (aggregates) can be dried to obtain a powder of the polymer microparticles.

[0076] As described above, the polymer microparticles can provide a resin composition having excellent fluidity. In addition, as described below, the polymer microparticles can be mixed with polyvinyl chloride (PVC) to provide a resin composition capable of providing a molded article having excellent impact resistance. In other words, the polymer microparticles can be suitably used as a modifier for polyvinyl chloride. Therefore, one embodiment of the present invention can be said to be a modifier for polyvinyl chloride.

[0077] An embodiment of the present invention may be configured as follows: The elastic body has a graft portion grafted to the elastic body, A modifier for polyvinyl chloride, wherein the graft portion contains alkyl acrylate units and polyfunctional units in a total amount of 90% by weight or more, based on 100% by weight of constituent units.

[0078] [2. Powder] The powder containing the polymer microparticles described in the above section [1. Polymer microparticles] is also one embodiment of the present invention. Since the powder has the above-mentioned constitution, it has the advantage of being able to provide a molded article having excellent low-temperature impact resistance. For example, a resin composition can be obtained by blending (adding) the powder to any resin. The molded article obtained by molding the resin composition has the advantage of being excellent in low-temperature impact resistance. Furthermore, since the powder has the above-mentioned constitution, it also has the advantage of being excellent in powder properties.

[0079] In this specification, the term "particulate material" includes both powder and granules, and refers to an aggregate of powder, granules, etc. In addition, when making a particular distinction, "powder" refers to a material having a volume average particle diameter of 0.01 mm to 0.1 mm, and "granules" refers to a material having a volume average particle diameter of 0.1 mm to 10 mm. However, the particulate material may contain coarse particles of 10 mm or more. The "volume average particle diameter" in the range of less than 10 μm can be measured using a dynamic light scattering (DLS) particle size distribution analyzer Nanotrac WaveII-EX150 (manufactured by Microtrack Bell Co., Ltd.), and the "volume average particle diameter" in the range of 10 μm or more can be measured using a laser diffraction particle size distribution analyzer Microtrack MT3000II (manufactured by Microtrack Bell Co., Ltd.).

[0080] (2-1. Other optional ingredients) The powder may contain optional components other than the polymer microparticles, as necessary. Examples of the optional components include curing agents, colorants such as pigments and dyes, extender pigments, pigment dispersants, UV absorbers, the above-mentioned antioxidants, heat stabilizers (gelling inhibitors), plasticizers, leveling agents, defoamers, silane coupling agents, antistatic agents, flame retardants, lubricants, viscosity reducers, viscosity adjusters, thixotropic agents, low-shrinkage agents, inorganic fillers, organic fillers, thermoplastic resins, drying agents, dispersants, thermal conductivity improvers, water binding agents, anti-sagging agents, color separation inhibitors, anti-settling agents, coating wear adjusters, surface adjusters, monobasic organic acids, camphor, castor oil, etc.

[0081] These other optional components can be added at any stage in the production of the powder or granule. For example, they may be added during the production (polymerization) of the polymer microparticles, they may be added to the aqueous latex of the polymer microparticles, or they may be added to the powder or granule.

[0082] (2-2. Manufacturing method of powder and granular materials) The method for producing the powder or granule of the present invention is not particularly limited as long as it can produce a powder or granule containing fine polymer particles. For example, the following embodiments are preferred: A preparation step of preparing polymer microparticles; an aggregating step of aggregating the polymer fine particles; a drying step of drying the aggregate obtained in the aggregation step.

[0083] (Preparation process) Specific examples of the preparation process are the same as those described in the above section (1-4. Method for producing polymer microparticles), and therefore the description is incorporated herein by reference and will not be described here.

[0084] (agglomeration process) The aggregation step is not particularly limited as long as it can finally obtain an aggregate of polymer fine particles.

[0085] The method of aggregating the polymer microparticles is not particularly limited. Examples of the method of aggregating the polymer microparticles include known methods such as a method using a coagulant, a method using a solvent, and a method of spraying an aqueous latex of polymer microparticles. Here, the mixture containing the aggregate of polymer microparticles and the aqueous solvent obtained by aggregating the polymer microparticles in the aqueous latex is also called a slurry.

[0086] As a method for aggregating the polymer fine particles, it is preferable to adopt a method using a coagulant, in other words, it is preferable to use a coagulant in the aggregating step.

[0087] Examples of the coagulant include an aqueous solution of an inorganic salt, an aqueous solution of an inorganic acid, an aqueous solution of an organic salt, an aqueous solution of an organic acid, and a polymeric coagulant.

[0088] Examples of inorganic salts include chloride salts, bromide salts, iodide salts, sulfate salts, nitrate salts, ammonium salts, and phosphate salts. Specific examples of inorganic salts include sodium chloride, potassium chloride, lithium chloride, sodium bromide, potassium bromide, lithium bromide, potassium iodide, sodium iodide, potassium sulfate, sodium sulfate, ammonium sulfate, ammonium chloride, sodium nitrate, potassium nitrate, calcium chloride, ferrous sulfate, magnesium sulfate, zinc sulfate, copper sulfate, barium chloride, ferrous chloride, ferric chloride, magnesium chloride, ferric sulfate, aluminum sulfate, potassium alum, and iron alum.

[0089] Examples of inorganic acids include hydrochloric acid, sulfuric acid, nitric acid, and phosphoric acid.

[0090] The coagulant may be used alone or in combination of two or more. As the coagulant, an aqueous solution of a monovalent or divalent inorganic salt or an inorganic acid such as sodium chloride, potassium chloride, sodium sulfate, ammonium chloride, calcium chloride, magnesium chloride, magnesium sulfate, barium chloride, hydrochloric acid, or sulfuric acid can be suitably used. There is no particular limitation on the method of adding the coagulant, and it can be added all at once, in portions, or continuously.

[0091] As the coagulant, only one of the above-mentioned compounds may be used, or two or more of them may be used in combination. As the coagulant, among the above-mentioned compounds, an aqueous solution of monovalent or divalent inorganic salt or inorganic acid such as sodium chloride, potassium chloride, sodium sulfate, ammonium chloride, calcium chloride, magnesium chloride, magnesium sulfate, barium chloride, hydrochloric acid, or sulfuric acid can be preferably used. There is no particular limitation on the method of adding the coagulant, and it can be added all at once, added in portions, or added continuously.

[0092] In one embodiment of the present invention, the polymer microparticles can be aggregated by contacting the aqueous latex containing the polymer microparticles with a coagulant or a solution of the coagulant (e.g., an aqueous solution). The method of contacting the aqueous latex containing the polymer microparticles with the coagulant or the solution of the coagulant is not particularly limited. Examples of the method include (i) a method of contacting the aqueous latex containing the polymer microparticles with a coagulant or a solution of the coagulant, and (ii) (ii-a) a method of contacting droplets containing polymer microparticles obtained by spraying the aqueous latex containing the polymer microparticles with (ii-b) a coagulant or a solution of the coagulant, or a solution of the coagulant solution.

[0093] In one embodiment of the present invention, a slurry containing agglomerates of polymeric particles can be obtained by contacting an aqueous latex containing polymeric particles with a coagulant or a solution of a coagulant.

[0094] In the course of intensive research, the present inventor independently and surprisingly found that a powdery granule having excellent powder characteristics can be obtained by setting the temperature (aggregation temperature) at or below room temperature (for example, 5°C to 10°C) when contacting an aqueous latex containing polymer fine particles with a coagulant or a solution of the coagulant. Conventionally, room temperature (for example, 23°C) has been adopted as the aggregation temperature of polymer fine particles. This is because the higher the temperature, the better the aggregation efficiency of the polymer fine particles. However, according to the findings of the present inventor, in the case of polymer fine particles in which the graft portion contains a total of 90% by weight or more of alkyl acrylate units and polyfunctional units in 100% by weight of the constituent units, as described above, a powdery granule having excellent powder characteristics can be obtained by setting the aggregation temperature at or below room temperature. It can be said that such findings are findings that could not be predicted from the prior art in which a temperature higher than room temperature was adopted as the aggregation temperature.

[0095] In one embodiment of the present invention, the aggregation temperature in the aggregation step is preferably 23° C. or lower, more preferably 20° C. or lower, further preferably 15° C. or lower, and particularly preferably 10° C. or lower.

[0096] From the viewpoint of aggregation efficiency of the polymer microparticles, the aggregation temperature in the aggregation step is preferably 0°C or higher, more preferably 1°C or higher, further preferably 3°C or higher, and particularly preferably 5°C or higher.

[0097] The aggregating step may further include a heat treatment step of heat-treating (heating) the slurry. By carrying out the heat treatment step, it is possible to obtain a powder having more excellent powder properties.

[0098] Since a powder having even more excellent powder properties can be obtained, the temperature of the slurry in the heat treatment step (heat treatment temperature) is preferably 70° C. or higher, more preferably 75° C. or higher, and even more preferably 80° C. or higher. The temperature of the slurry in the heat treatment step (heat treatment temperature) is preferably less than 100° C., more preferably 95° C. or lower, and even more preferably 90° C. or lower.

[0099] In the heat treatment step, the time for which the slurry is held at the heat treatment temperature is referred to as the “heat treatment time.” Since a powder having even more excellent powder properties can be obtained, the heat treatment time of the slurry in the heat treatment step is preferably 5 to 120 seconds, more preferably 5 to 60 seconds, even more preferably 5 to 40 seconds, and particularly preferably 5 to 20 seconds.

[0100] The agglomeration step may further include a recovery step of recovering the resulting agglomerates from the slurry.

[0101] The recovery step is not particularly limited as long as it can separate the aqueous solvent of the slurry from the aggregates, and any known method can be used. Examples of the recovery step include a method of filtering the slurry and a method of centrifugal dehydration of the slurry.

[0102] When a heat treatment step is performed, it is preferable to cool the slurry after the heat treatment step to room temperature (e.g., 23°C) and then recover the aggregates from the slurry. When the slurry is at room temperature (e.g., 23°C), filtration of the slurry and / or dehydration from the slurry becomes easy. As a result, a powder having even more excellent powder properties can be obtained.

[0103] (drying process) The drying step is a step of drying the aggregate of polymer microparticles obtained by the above-mentioned aggregation step. The method for drying the aggregate is not particularly limited, and examples thereof include static drying, flash drying, and freeze drying.

[0104] In this specification, the term "static drying" refers to a mode in which an aggregate of polymer fine particles is dried by being statically left in a container such as an oven.

[0105] In this specification, the term "airflow drying" refers to a mode in which the aggregates are dried while being airborne in a certain space. The airflow drying method is not particularly limited, and any conventionally known method can be used. One example of airflow drying is a method in which the aggregates are placed in a container and a gas at a predetermined temperature is fed into the container to dry the aggregates while being airborne in the container.

[0106] In this specification, the term "airflow drying" refers to drying the aggregates while they are airborne in a certain space. The airflow drying method is not particularly limited, and any conventionally known method can be used. One example of airflow drying is a method in which the aggregates are placed in a container and a gas at a predetermined temperature is fed into the container to dry the aggregates while they are airborne in the container.

[0107] The method of freeze-drying is not particularly limited, and any conventionally known method can be used. When freeze-drying is used as the drying step, the drying step can be easily carried out at 0° C. or lower.

[0108] (Cleaning process) Between the aggregating step and the drying step, a washing step of washing the aggregate obtained in the aggregating step with washing water (for example, tap water, ion-exchanged water or pure water) may be further included.

[0109] As described below, the present powder can be mixed with polyvinyl chloride (PVC) to provide a resin composition that can provide a molded article with excellent impact resistance. In other words, the present powder can be suitably used as a modifier for polyvinyl chloride.

[0110] An embodiment of the present invention may be configured as follows: The elastic body has a graft portion grafted to the elastic body, The graft portion contains alkyl acrylate units and polyfunctional units in a total amount of 90% by weight or more based on 100% by weight of the structural units, A granular polyvinyl chloride modifier.

[0111] [3. Resin composition] A resin composition containing the polymer microparticles described in the above-mentioned section [1. Polymer microparticles] or the powder particles described in the above-mentioned section [2. Powder particles] and a matrix resin is also one embodiment of the present invention. Since this resin composition has the above-mentioned configuration, it has the advantage that it can provide a molded product having excellent low-temperature impact resistance.

[0112] (Matrix resin) Examples of the matrix resin include thermoplastic resins such as acrylic polymers, vinyl copolymers, polycarbonates, polyamides, polyesters, polyphenylene ethers, polyurethanes, and polyvinyl acetates, etc. These may be used alone or in combination of two or more.

[0113] The acrylic polymer is a polymer mainly composed of a structural unit made of an acrylic acid ester monomer. The acrylic acid ester monomer preferably has an ester moiety having 1 to 20 carbon atoms. Examples of the acrylic polymer include (a) a homopolymer of an acrylic acid ester monomer, and (b) a copolymer of an acrylic acid ester monomer with a monomer such as an unsaturated fatty acid, an acrylamide monomer, a maleimide monomer, or vinyl acetate, or a vinyl copolymer (hereinafter also referred to as an acrylic copolymer).

[0114] The vinyl copolymer is obtained by copolymerizing a mixture of vinyl monomers containing at least one monomer selected from the group consisting of an aromatic vinyl monomer, a cyanide vinyl monomer, and an unsaturated carboxylic acid alkyl ester monomer. The mixture of vinyl monomers may further contain other monomers copolymerizable with the above-mentioned monomers.

[0115] Specific examples of vinyl copolymers include polyvinyl chloride (PVC), chlorinated polyvinyl chloride, polystyrene, styrene-acrylonitrile copolymer, styrene-acrylonitrile-N-phenylmaleimide copolymer, α-methylstyrene-acrylonitrile copolymer, polymethyl methacrylate, methyl methacrylate-styrene copolymer, etc. These may be used alone or in combination of two or more.

[0116] Examples of the polyester include polyethylene terephthalate and polybutylene terephthalate. Examples of the polyester also include biodegradable plant-derived resins such as aliphatic polyesters and polylactic acid.

[0117] The matrix resin is preferably polyvinyl chloride. This configuration has the advantage that it is possible to provide a resin composition having excellent flowability and a molded article having excellent impact resistance and transparency.

[0118] (Other optional ingredients) The resin composition may contain other optional components other than the matrix resin, as necessary. Examples of the other optional components include a curing agent, a coloring agent such as a pigment or dye, a body pigment, a pigment dispersant, an ultraviolet absorber, the above-mentioned antioxidant, a heat stabilizer (gelling inhibitor), a plasticizer, a leveling agent, an antifoaming agent, a silane coupling agent, an antistatic agent, a flame retardant, a lubricant, a viscosity reducing agent, a viscosity adjusting agent, a thixotropic agent, a shrinkage reducing agent, an inorganic filler, an organic filler, a thermoplastic resin, a drying agent, a dispersing agent, a thermal conductivity improving agent, a water binding agent, an anti-sagging agent, a color separation preventing agent, an anti-settling agent, a coating wear adjusting agent, a surface adjusting agent, a monobasic organic acid, camphor, castor oil, etc.

[0119] These other optional components can be added at any stage of the production of the resin composition. For example, they may be added during the production (polymerization) of the polymer fine particles, added to the aqueous latex of the polymer fine particles, added to the powder, added to the resin before being mixed with the polymer fine particles, or added to the resin composition.

[0120] (Method of producing resin composition) A method for producing a resin composition according to an embodiment of the present invention includes a step of mixing the polymer fine particles described in [1. Polymer fine particles] or the powdered material described in [2. Powdered material] with a matrix resin. This method makes it possible to obtain a resin composition in which the polymer fine particles are uniformly dispersed in the matrix resin.

[0121] Regarding the method for producing the resin composition, various components and specific steps are not particularly limited, and the above explanations are appropriately used.

[0122] For example, a resin composition can be obtained by mixing the powder particles of polymer fine particles with a matrix resin. The specific method for mixing the powder particles of polymer fine particles with the matrix resin is not particularly limited, and examples thereof include a method using a rotation / revolution mixer, a planetary mixer, a disperser, etc. A preferred method for mixing the powder particles of polymer fine particles with the matrix resin is, for example, a method in which the powder particles of polymer fine particles are mixed with a rotation / revolution mixer at 2000 rpm for 40 minutes.

[0123] Furthermore, the method for producing the resin composition may include a step of washing the obtained resin composition. By washing the resin composition, a resin composition containing fewer impurities can be produced.

[0124] Furthermore, the method for producing a resin composition according to one embodiment of the present invention may include other steps. In addition to the above-mentioned steps, the method may include a step of heating the obtained resin composition, devolatilizing and drying it. Various methods can be used for such a step, and there is no particular limitation. Examples of the step of devolatilizing and drying include heating and vacuum devolatilization.

[0125] [4. Molded body] A molded article obtained by molding the resin composition described in the above section [3. Resin composition] is also one embodiment of the present invention. The molded article has an advantage of being excellent in low-temperature impact resistance.

[0126] (Impact resistance of molded body) The IZOD test result for the molded product at 0°C was 27 kJ / m 2 More preferably, it is 28 kJ / m or more. 2 More preferably, it is 29 kJ / m or more. 2 More preferably, it is 30 kJ / m or more. 2 More preferably, it is 31 kJ / m or more. 2 More preferably, it is 32 kJ / m or more. 2 More preferably, it is 33 kJ / m or more. 2 More preferably, it is 34 kJ / m or more. 2 More preferably, it is 35 kJ / m or more. 2 More preferably, it is 36 kJ / m or more. 2 More preferably, it is 37 kJ / m or more. 2 It is particularly preferable that the IZOD test result of the molded product at 0° C. is 27 kJ / m or more. It can be said that the larger the value of the IZOD test result of the molded product at 0° C., the more excellent the low-temperature impact resistance of the molded product. 2When the IZOD value is larger than 1000, the molded article has excellent low-temperature impact resistance. The measurement method for the IZOD test of the molded article at ° C. will be described in detail in the Examples below.

[0127] (Method of Manufacturing Molded Product) In the method for producing a molded article according to one embodiment of the present invention, the molded article can be obtained by molding the resin composition described in the section [3. Resin composition].

[0128] The method for producing the present molded article is not particularly limited, but examples thereof include rolling, pressing, extrusion molding, and injection molding. EXAMPLES

[0129] Hereinafter, one embodiment of the present invention will be described in more detail with reference to examples and comparative examples, but the present invention is not limited thereto. One embodiment of the present invention can be practiced with appropriate modifications within the scope of the above or below-mentioned purpose, and all of these modifications are included in the technical scope of the present invention. In the following, unless otherwise specified, "parts" means "parts by weight" and "%" means "% by weight".

[0130] First, various measurement and evaluation methods will be described.

[0131] [Measurement and evaluation methods] (Method for measuring volume average particle size of polymer fine particles) Using an aqueous latex containing polymer microparticles as a sample, the volume average particle size of the polymer microparticles was measured on a volume basis using a particle size distribution measuring device using dynamic light scattering ("Nanotrac Wave-EX150" manufactured by Nikkiso Co., Ltd.).

[0132] (Powder properties of polymer fine particles) Approximately 20 g of the polymer microparticle powder obtained in each Example and Comparative Example was spread on a sheet of paper, and the particle size range of the powder was measured using a scaled ruler. The powder properties of the powder were then evaluated according to the following criteria. Note that the larger the number, the better the powder properties. 3: The particle size range of the powder is about 0.1 mm to about 0.5 mm. 2: The particle size range of the powder is about 0.1 mm to about 2.0 mm. 1: The particle size range of the powder is about 0.1 mm to about 5.0 mm.

[0133] (Creating test pieces for measuring physical properties) 100 parts of polyvinyl chloride (Kaneka Corporation, "Kanevinyl S-1007") as a matrix resin, 1.0 part of a tin-based stabilizer (Nitto Kasei Corporation, "TVS#8831"), 0.8 parts of a lubricant (Emery Oleochemicals Japan, Inc., "Loxiol GH-4"), and 0.2 parts of a lubricant (Clariant Japan, Inc., "Wax-E") were mixed, and the resulting mixture was heated to 110°C with stirring. The resulting mixture was then cooled to room temperature (23°C) (total amount 102.0 parts).

[0134] To the resulting mixture, 10 parts of polymer fine particles (impact modifier) ​​obtained in each of the following Examples or Comparative Examples were added per 100 parts of polyvinyl chloride to obtain a resin composition. The resulting resin composition was kneaded for 5 minutes at 155°C using a kneader equipped with two rolls ("8-inch mixing roll" manufactured by Nippon Roll Mfg. Co., Ltd.) to produce a sheet (molded product). Thereafter, the composition was pressurized at 70 kgf / cm at 180°C using a heat press machine (37-ton press manufactured by Shinto Metal Works). 2 The sheet was pressed at a pressure of 1.0 mm for 15 minutes to prepare a test piece (thickness 5 mm) for measuring physical properties. The obtained test piece complies with the JIS K 7110 standard.

[0135] (Measurement of impact resistance) Using the obtained impact resistance test pieces (thickness 5 mm), an IZOD test was carried out with a V notch and at 23° C. or 0° C. to measure the impact resistance in accordance with JIS K 7110.

[0136] (Measurement of B method flow) The resin composition was filled into a cylinder at room temperature and 190°C, and a load of 300 kgf / cm was applied from a die: 1 mmφ×10 mm. 2 By extruding at 100°C, the amount of resin composition discharged from the die (cm 3 ) was measured. 3 ) to the discharge volume (cm 3 ) by the time (s) required for the material to be discharged from the die, yielding the flow rate (cm 3 / sec×10 -2 In this specification, the unit "(cm 3 / sec×10 -2 )" is "{(cm 3 / sec)×10 -2}".

[0137] Example 1 <Production of elastic body (polymerization)> 160 parts of water and 0.4 parts of tripotassium phosphate were charged into a pressure-resistant polymerization vessel equipped with a stirrer. After the temperature inside the pressure-resistant polymerization vessel was raised to 40°C, ferrous sulfate (FeSO 4 7H 2 0.0048 parts of sodium ethylenediaminetetraacetate (EDTA·2Na), 0.0079 parts of disodium ethylenediaminetetraacetate (EDTA·2Na), and 0.02 parts of sodium formaldehyde sulfoxylate were added to the pressure polymerization vessel. Next, after degassing the pressure polymerization vessel, 1.8 parts of sodium oleate were added to the pressure polymerization vessel, and further, a monomer mixture for forming an elastomer consisting of 90 parts of butadiene (Bd) and 10 parts of β-farnesene (FA) was added to the pressure polymerization vessel all at once. Then, 0.06 parts of paramenthane hydroperoxide were added to the pressure polymerization vessel to start polymerization of the elastomer. During the polymerization, sodium formaldehyde sulfoxylate, paramethane hydroperoxide, and sodium oleate were appropriately added. At the 16th hour after the start of polymerization, the polymerization conversion rate reached 99%, and a latex containing an elastomer (butadiene-based rubber) (BBR-1) with a volume average particle diameter of 67 nm was obtained. The solids concentration of the latex was 39%.

[0138] <Production of graft portion (polymerization)> 231 parts latex containing elastomer (BBR-1) (90 parts elastomer), Water and 0.25 parts of sodium oleate were charged to a polymerization vessel equipped with a stirrer. The amount of water charged here was such that the total amount of water contained in 231 parts of latex (BBR-1) was 250 parts. Next, the gas in the polymerization vessel was replaced with nitrogen, and the temperature in the polymerization vessel was raised to 60°C. Next, ferrous sulfate (FeSO 4 7H 2 0.0056 parts of EDTA·2Na, 0.0094 parts of EDTA·2Na, and 0.06 parts of sodium formaldehyde sulfoxylate were added to the polymerization vessel. Then, a mixture of the monomer mixture for forming the graft portion (a mixture of 10 parts of butyl acrylate (BA) and 0.05 parts of allyl methacrylate) and 0.04 parts of a polymerization initiator (t-butyl hydroperoxide) was continuously added to the polymerization vessel over 50 minutes to polymerize the graft portion. During the polymerization, sodium formaldehyde sulfoxylate, t-butyl hydroperoxide, and sodium oleate were appropriately added. By this operation, a latex containing polymer fine particles (BBG-1) with a volume average particle diameter of 75 nm was obtained. The polymerization conversion rate was 99%, and the solid concentration of the latex was 28%.

[0139] <Production of powders and granules> (solidification process) To the obtained latex containing polymer microparticles (BBG-1), 2.0 parts of an emulsified antioxidant was added, and further 2.0 parts of calcium chloride was added at 5° C. to 10° C. to coagulate the polymer microparticles. After adjusting the amount of water for the obtained slurry so that the slurry concentration became 10%, the slurry was heat-treated at 80° C. to 90° C. for 60 seconds (heat treatment step).

[0140] (Recovery process) The slurry was then cooled to room temperature, dehydrated, and the coagulated material was collected.

[0141] (drying process) The obtained coagulated material was dried at 50° C. to obtain powdered polymer particles, that is, granules.

[0142] Using the obtained powder, a resin composition was produced according to the above-mentioned method (preparation of test pieces for measuring physical properties), and further, test pieces for measuring physical properties were produced. The obtained test pieces were measured for impact resistance and flow rate according to the above-mentioned method. The results are shown in Table 1 together with the composition of the polymer microparticles.

[0143] Example 2 <Production of elastic body (polymerization)> 160 parts of water and 0.4 parts of tripotassium phosphate were charged into a pressure-resistant polymerization vessel equipped with a stirrer. After the temperature inside the pressure-resistant polymerization vessel was raised to 40°C, ferrous sulfate (FeSO 4 7H 2 O), 0.0048 parts, disodium ethylenediaminetetraacetate (EDTA·2Na), and 0.02 parts of sodium formaldehyde sulfoxylate were added to the pressure polymerization vessel. Next, after degassing the pressure polymerization vessel, 1.8 parts of sodium oleate were added to the pressure polymerization vessel, and further, an elastomer-forming monomer consisting of 100 parts of butadiene was added to the pressure polymerization vessel all at once. Then, 0.06 parts of paramenthane hydroperoxide were added to the pressure polymerization vessel to start polymerization of the elastomer. During the polymerization, sodium formaldehyde sulfoxylate, paramethane hydroperoxide, and sodium oleate were appropriately added. At the 15th hour after the start of polymerization, the polymerization conversion rate reached 96%, and a latex containing an elastomer (BBR-2) consisting of butadiene-based rubber was obtained. The volume average particle diameter of the elastomer in the latex was 83 nm, and the solid concentration of the latex was 37%.

[0144] <Production of grafted portion (polymerization) and production of powder and granule> A latex containing polymer fine particles (BBG-2) was obtained in the same manner as in Example 1, except that a latex containing elastic body (BBR-2) was used in an amount equivalent to 90 parts of elastic body instead of the latex containing elastic body (BBR-1). The polymerization conversion rate was 99%, the volume average particle size of the polymer fine particles in the latex was 85 nm, and the solid content concentration of the latex was 28%.

[0145] Further, a powder was obtained in the same manner as in Example 1. Various physical properties were evaluated using the obtained powder, and the results are shown in Table 1 together with the composition of the polymer microparticles.

[0146] Comparative Example 1 <Elastic body> As in Example 2, a latex containing an elastomer (butadiene rubber) (BBR-2) was used.

[0147] <Production of graft portion (polymerization)> 189 parts of the latex containing the elastomer (BBR-2) (70 parts of the elastomer) and water were charged into a polymerization vessel equipped with a stirrer. The amount of water charged was such that the total amount of the water contained in the 189 parts of the latex (BBR-2) was 250 parts. Next, the gas in the polymerization vessel was replaced with nitrogen, and the temperature in the polymerization vessel was raised to 60°C. Next, ferrous sulfate (FeSO 4 7H 2 0.0056 parts of EDTA·2Na, 0.0094 parts of EDTA·2Na, and 0.2 parts of sodium formaldehyde sulfoxylate were added to the polymerization vessel. Then, 2 parts of sodium sulfate and 0.25 parts of sodium oleate were added to the polymerization vessel. Next, a mixture of monomer mixture for forming the graft part (a mixture of 20 parts of methyl methacrylate (MMA), 5 parts of butyl acrylate (BA), and 5 parts of styrene (St)) and 0.1 parts of polymerization initiator (t-butyl hydroperoxide) was continuously added to the polymerization vessel over 150 minutes to polymerize the graft part. During the polymerization, sodium formaldehyde sulfoxylate, t-butyl hydroperoxide, and sodium oleate were appropriately added. By this operation, a latex containing polymer fine particles (BBG-3) was obtained. The polymerization conversion rate was 99%, the volume average particle diameter of the polymer fine particles in the latex was 190 nm, and the solid concentration of the latex was 28%.

[0148] <Production of powders and granules> A powder was obtained in the same manner as in Example 1. Various physical properties were evaluated using the obtained powder, and the results are shown in Table 1 together with the composition of the polymer microparticles.

[0149] Comparative Example 2 <Elastic body> As in Example 2, a latex containing an elastomer (butadiene rubber) (BBR-2) was used.

[0150] <Production of graft portion (polymerization)> 189 parts of the latex containing the elastomer (BBR-2) (70 parts of the elastomer) and water were charged into a polymerization vessel equipped with a stirrer. The amount of water charged was such that the total amount of the water contained in the 189 parts of the latex (BBR-2) was 250 parts. Next, the gas in the polymerization vessel was replaced with nitrogen, and the temperature in the polymerization vessel was raised to 60°C. Next, ferrous sulfate (FeSO 4 7H 2 0.0056 parts of EDTA·2Na, 0.0094 parts of EDTA·2Na, 0.2 parts of sodium formaldehyde sulfoxylate, and 0.25 parts of sodium oleate were added to the polymerization vessel. Then, a mixture of monomer mixture for forming graft part (mixture of 20 parts of methyl methacrylate (MMA), 5 parts of butyl acrylate (BA), and 5 parts of styrene (St)) and 0.1 parts of polymerization initiator (t-butyl hydroperoxide) was continuously added to the polymerization vessel over 150 minutes to polymerize the graft part. During the polymerization, sodium formaldehyde sulfoxylate, t-butyl hydroperoxide, and sodium oleate were appropriately added. By this operation, a latex containing polymer fine particles (BBG-4) was obtained. The polymerization conversion rate was 99%, the volume average particle diameter of the polymer fine particles in the latex was 85 nm, and the solid concentration of the latex was 28%.

[0151] <Production of powders and granules> A powder was obtained in the same manner as in Example 1. Various physical properties were evaluated using the obtained powder, and the results are shown in Table 1 together with the composition of the polymer microparticles.

[0152] Comparative Example 3 <Production of elastic body (polymerization)> 200 parts of water, 0.2 parts of tripotassium phosphate, and 5 parts of sodium lauryl sulfate were charged into a polymerization vessel equipped with a stirrer. Next, the gas in the polymerization vessel was replaced with nitrogen, and the temperature in the polymerization vessel was raised to 60°C. Next, ferrous sulfate (FeSO 4 7H 2 In the polymerization vessel, 0.0094 parts of ethylenediaminetetraacetate (EDTA·2Na), 0.0156 parts of disodium ethylenediaminetetraacetate (EDTA·2Na), and 0.5 parts of sodium formaldehyde sulfoxylate were added, and further, a monomer mixture for forming an elastomer consisting of 100 parts of β-farnesene (FA) and 5 parts of 1,3-butylene glycol dimethacrylate was added all at once to the polymerization vessel. Next, paramenthane hydroperoxide was appropriately added in portions to the polymerization vessel. By this operation, a latex containing an elastomer (BFR-1) consisting of β-farnesene-based rubber was obtained. The polymerization conversion rate was 99%, the volume average particle size of the elastomer in the latex was 25 nm, and the solid concentration of the latex was 34%.

[0153] <Production of graft portion (polymerization)> 206 parts of the latex containing the elastomer (BFR-1) (70 parts of the elastomer) and water were charged into a polymerization vessel equipped with a stirrer. The amount of water charged was such that the total amount of water contained in the 206 parts of the latex (BFR-1) was 300 parts. Next, the gas in the polymerization vessel was replaced with nitrogen, and the temperature in the polymerization vessel was raised to 60°C. Next, ferrous sulfate (FeSO 4 7H 2 0.0056 parts of EDTA·2Na, 0.0094 parts of EDTA·2Na, and 0.2 parts of sodium formaldehyde sulfoxylate were added to the polymerization vessel. Next, as the first stage of graft polymerization, a mixture of the first graft forming monomer (15 parts of styrene (St) only) and 0.16 parts of a polymerization initiator (t-butyl hydroperoxide) was continuously added to the polymerization vessel over 75 minutes, and the first stage of graft polymerization was carried out for 30 minutes.

[0154] Thereafter, as the second stage of graft polymerization, a mixture of the second graft forming monomer (only 15 parts of methyl methacrylate (MMA)) and 0.08 parts of polymerization initiator (t-butyl hydroperoxide) was continuously added to the polymerization vessel over 75 minutes to carry out the second stage of polymerization of the graft portion. During the polymerization, sodium formaldehyde sulfoxylate and t-butyl hydroperoxide were appropriately added to the polymerization vessel. By this operation, a latex containing polymer fine particles (BFG-1) was obtained. The polymerization conversion rate was 99%, the volume average particle diameter of the polymer fine particles in the latex was 26 nm, and the solid concentration of the latex was 25%.

[0155] <Production of powders and granules> A powder was obtained in the same manner as in Example 1. Various physical properties were evaluated using the obtained powder, and the results are shown in Table 1 together with the composition of the polymer microparticles.

[0156] [Table 1]

[0157] <Consideration> The polymer microparticles according to one embodiment of the present invention have an elastomer and a graft portion grafted to the elastomer, and the graft portion contains only alkyl acrylate units and polyfunctional units as constituent units. Therefore, the polymer microparticles according to one embodiment of the present invention can provide a molded product having excellent low-temperature impact resistance, as shown in Table 1. Furthermore, the polymer microparticles according to one embodiment of the present invention can also provide a powdered product having excellent powder properties, as shown in Table 1. [Industrial Applicability]

[0158] The polymer microparticles according to one embodiment of the present invention can be preferably used in adhesives, coating materials, molded articles, films, etc. by being blended with a matrix resin. As application fields, the polymer microparticles can be preferably used in stationery applications, food packaging applications, electrical and electronic applications, building materials applications, vehicle applications, etc.

Claims

1. The elastic body has a graft portion grafted to the elastic body, The graft portion is a polymer fine particle containing alkyl acrylate units and polyfunctional units in a total amount of 90% by weight or more based on 100% by weight of constituent units.

2. 2. The polymer microparticle according to claim 1, wherein the elastomer comprises one or more structural units selected from the group consisting of farnesene units, diene units other than the farnesene units, vinyl units and polyfunctional units.

3. 2. The polymer microparticle according to claim 1, wherein the elastomer comprises (i) a farnesene unit and (ii) one or more structural units selected from the group consisting of a diene unit other than the farnesene unit, a vinyl unit and a polyfunctional unit.

4. The elastic body contains, based on 100% by weight of the constituent units, Contains 5.0% to 99.9% by weight of farnesene units; and The polymer microparticles according to claim 1, comprising, in total, 0.1% by weight to 95.0% by weight of one or more constituent units selected from the group consisting of diene units other than the farnesene units, vinyl units and polyfunctional units.

5. The elastic body contains, based on 100% by weight of the constituent units, The composition contains 0% by weight to 95.0% by weight of diene units other than the farnesene units, The vinyl unit is contained in an amount of 0% by weight to 50.0% by weight, and The polymer microparticles according to claim 4, comprising 0 to 20.0% by weight of said polyfunctional units.

6. 2. The polymer microparticle according to claim 1, wherein the alkyl acrylate unit in the graft moiety is a butyl acrylate unit.

7. A powder or granule comprising the polymer fine particles according to claim 1.

8. A resin composition comprising: (i) the polymer fine particles according to any one of claims 1 to 6; or the powder or granule according to claim 7; and (ii) a matrix resin.

9. The resin composition according to claim 8 , wherein the matrix resin is polyvinyl chloride.

10. A molded article obtained by molding the resin composition according to claim 8.

Citation Information

Patent Citations

  • Vinyl chloride resin composition

    JP1991259942A

  • Coated polymer particles, resin modifier, rubber composition, and tire

    WO2017038724A1